2003
DOI: 10.1592/phco.23.15.1668.31951
|View full text |Cite
|
Sign up to set email alerts
|

Fatality Related to a 30‐g Venlafaxine Overdose

Abstract: A 30-g venlafaxine overdose resulted in death for a 39-year-old woman whose 43-day clinical course was highlighted by refractory hypotension and the resulting complications of bowel ischemia and perforation. Her venlafaxine and O-desmethylvenlafaxine levels, analyzed by high-performance liquid chromatography one day after ingestion, were 21.82 mg/L (therapeutic range 0.1-0.5 mg/L) and 3.33 mg/L (0.2-0.4 mg/L), respectively. These levels remained elevated for over 7 days. Postulated explanations for these exten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
3

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 19 publications
1
18
0
3
Order By: Relevance
“…Emerging toxicological and epidemiological data suggest that venlafaxine has a more hazardous toxicity profile than SSRIs, with greater propensity to cause arrhythmias and seizures (Whyte et al 2003). Deaths have been reported after venlafaxine ingestion (Mazur et al 2003), and it has been suggested that venlafaxine should be used with the same caution as TCAs in patients who are at high immediate risk of self-poisoning (Whyte et al 2003). The question of whether children and adolescents display a differential risk of toxicity outcome has not been systematically examined.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging toxicological and epidemiological data suggest that venlafaxine has a more hazardous toxicity profile than SSRIs, with greater propensity to cause arrhythmias and seizures (Whyte et al 2003). Deaths have been reported after venlafaxine ingestion (Mazur et al 2003), and it has been suggested that venlafaxine should be used with the same caution as TCAs in patients who are at high immediate risk of self-poisoning (Whyte et al 2003). The question of whether children and adolescents display a differential risk of toxicity outcome has not been systematically examined.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the HPLC-FLD method herein developed is reliable, accurate and reproducible over the wide calibration range proposed, including when a 10-fold dilution of plasma samples with blank plasma is necessary. Actually, according to various toxicological studies [45,[47][48][49] VEN and ODV concentrations can be higher than 1000 ng ml -1 (ULOQ) in intoxication cases, being necessary the sample dilution in order to accurately quantify these samples. However, most of VEN's methods reported in literature did not consider the study of the dilution integrity and, therefore, in most cases, these high concentrations were not covered or a more narrow calibration range was defined.…”
Section: Precision and Accuracymentioning
confidence: 99%
“…Overdoses with VEN have been associated with several adverse effects such as sedation, tachycardia, seizures, hypotension, hypertension and serotonin syndrome [7][8][9][10][11][12][13] and fatal overdoses have been reported for VEN alone or in combination with other compounds [14,15].…”
Section: Introductionmentioning
confidence: 99%